Faktor Penyebab Intrusi Air Laut Terhadap Air Tanah Pada Akuifer Dalam Di Kota Semarang - Edy Suhartono; Purwanto Purwanto; Suripin Suripin (Politeknik Negeri Semarang, 2013)
Semarang is a beach city that is potential for sea water intrusion process happened. Correlation to the sustainable development programs in our country especially environment-conservations aspect, it is important to be known, and need to be monitored and controlled.Contamination in land water is a serious probleme, becouse it makes water quality decrease. Sea water intrusion is one of contaminant resources to the land water that cause hight concentration of salt. It is identified by concentration level of chloride (Cl) that come from sea water by mass transportation process of chloride (Cl) to the land water, and so the volume of land water that is fullfill in quality standard limited. Focus of the research is identifying distributions of factor that cause sea water intrusions happened to the land water in inner aquifer in Semarang area. Method of research, by determining of monitoring wells of ESDM service as sample points, continued to measuring concentrations of chloride (Cl) continuously and identifies factor causes the intrusions. To describe the distributions is used the ArcGIS application programs, and to know correlations of chloride’s concentrations to time changes is used correlations statistics test. The result of research showed that sea water intrusions which are identified the chloride (Cl) concentrations and exceeded the quality standard (PERMENKES No. 492/MENKES/PER/IV/2010), in 1992 only one of them, that is monitory wells on STM Perkapalan, north of Semarang. And in 2013, the intrusions happened in 6 (six) areas, those are monitory wells on STM Perkapalan, PRPP, Pelabuhan Tanjung Mas, Simpang Lima, PT Panca Jaya and LIK Kaligawe located in areas of : Kecamatan west of Semarang, nort of Semarang, middle of Semarang and Gayamsari. Factors which cause sea water intrusions are : the increase of populations effects the water reserve decreases to be about 125,7 .106 m3, Land water head changes that caused by descending (sinking) of land , changings of land water surface level from sea level make the distributions of intrusion go to short -east direction, and there is correlation between Chloride’s concentrations level changes to the times changes by the constant of correlations about R = 0,704 to R = 0,997.